Self-inflicted accidental penile fracture: A rare case report in Indian scenario. - Singh, Harbhupinder; Singh, Harjinder; Kaur, Savleen; Singh, Gagandeep; Singh, Samrat; Singh, Ramandeep; Wasan, Anuj (GMC Patiala Journal of Research and Medical Education, 2024)
Penile fracture is a rare injury sustained during sexual intercourse. We report a rare case of 30 years old male who had accidental self-inflicted penile fracture , not related to masturbation or sexual intercourse. Diagnosed promptly on clinical assessment ,confirmed on medical imaging and managed surgically. Our case highlights the importance of maintaining a high index of suspicion to diagnose this rare condition even in absence of typical mechanism of injury in Indian scenario in order to ensure that such an injury is not missed.